Russian and Romanian gymnastics teams demonstrate the importance of classical ballet - Apatow, S. M. (2001)
In Eastern Bloc development programs, a selection process is used to locate children who have natural joint flexibility and body mechanics which are considered prerequisite for future progress in ballet or Olympic competition. Those selected then enter into a development program which integrates classical ballet based choreography training as a foundation for the correct execution of technical sports specific movement. Classical ballet training is considered the most advanced movement mechanics training in the world, providing a foundation for the development of joint strength, postural alignment and precision control of the human frame in space. In Eastern Bloc programs, approximately 45 minutes per day is committed to this training, 6 days per week.